Changes in various strength attributes in male collegiate rugby sevens players after a uniform resistance training program - Lee, H. J.; Chen, M. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Rugby sevens is a high-intensity team sport played on a field, where certain physical capabilities, particularly acceleration and countermovement jump (CMJ) height, are crucial as they have shown correlations with game statistics. The dynamic strength index (DSI), which is derived from the relative peak force of the CMJ and the isometric mid-thigh pull (IMTP), serves as a tool for guiding diagnostic training focused on maximal strength or ballistic exercises. Thus, this study aims to investigate the relationship between 10-meter sprint speed and various strength qualities, and to evaluate the impact of the same resistance training regimen on athletes with differing DSI and EI values. METHODS: Ten male collegiate rugby sevens athletes completed a 3-week training intervention consisting of sprint drills, weightlifting derivatives, combined free-weight resistance, and ballistic training. Athletes were tested on the 10-m sprint, squat jump (SJ), countermovement jump (CMJ), and isometric mid-thigh pull (IMTP) before (PRE) and after (POST) the intervention. Participants were ranked based on dynamic strength index (DSI) and elastic index (EI) then split into high and low groups (DSI-H vs DSI-L; EI-H vs EI-L). Independent t-tests compared mean differences in variables between the high and low DSI and EI groups. Statistical significance was set at p < .05. RESULTS: After the 3-week training, 10-m sprint velocity significantly increased in both DSI-H and DSI-L (5.16 ± 0.18 vs 5.48 ± 0.63 m/s, and 5.85 ± 0.38 vs 6.06 ± 0.30 m/s, respectively, p